ANALISIS NILAI TAMBAH DAN KELAYAKAN FINANSIAL AGROINDUSTRI TAHU DAN TEMPE DI KOTA METRO - Zakaria, Wan Abbas (Lampung University)
The objective of this research is to analyze the added value and financial feasibility of tofu and tempe smallscale agroindustries in Metro City. This study employs survey method involving primary and secondary data. The 4 respondents of tofu industries and 8 respondents of tempe industries were selected using simple random sampling. Added value analysis is used to investigate the feasibility of this venture. Some parameters for analysis include NPV, IRR, Net B/C, pay back period. The study suggests that small scale tofu and tempe agroindustries are profitable. They have high added value in addition to the labor absorption. Tofu and tempe agroindustry has profit margin of 44,19% and 26,15% respectively and added value of 56,89% and 34,19% of product value. Its is therefore, these industries are feasible. However, proportion of labor absorption is less than proportion of the profit margin. Both industries are sensitive from an increase in input and labor cost for 50% and decrease of in output price at 5%.